2015
DOI: 10.1063/1.4906758
|View full text |Cite
|
Sign up to set email alerts
|

Note: An improved driver section for a diaphragmless shock tube

Abstract: Improvements to equipment lifetime and measurement reproducibility have been made by modifying the actuating mechanism of a diaphragmless shock tube that is used for high temperature gas kinetic studies. The modifications have two major benefits while retaining the simplicity of the original apparatus. First, the reproducibility of shock wave generation has been greatly improved and is demonstrated with 50 nearly identical experiments on the dissociation of cyclohexene at T2 = 1765 ± 13 K and P2 = 120 ± 1 Torr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Experiments were performed behind incident shock waves in a diaphragmless shock tube (DFST) that created very reproducible and predictable reaction conditions. The DFST has been fully described previously [12]. The temperature, T 2 , and pressure, P 2 , behind the incident shock wave were calculated from the ideal shock relations, initial loading conditions and incident shock velocity, assuming frozen conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were performed behind incident shock waves in a diaphragmless shock tube (DFST) that created very reproducible and predictable reaction conditions. The DFST has been fully described previously [12]. The temperature, T 2 , and pressure, P 2 , behind the incident shock wave were calculated from the ideal shock relations, initial loading conditions and incident shock velocity, assuming frozen conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Roth et al [9] reported rate coefficients for dissociation of 2,5-dimethyl-1,5-hexadiene (25DM15HD), the reverse of reaction 1 (Note: all reaction numbers refer to Tables 1 and S2), from single pulse shock tube (SPST) experiments over 873-1073 K and obtained k 1 from calculated thermochemical quantities and the equilibrium constant. Bayraceken et al [10] obtained k 1 at 295 K from flash photolysis of 2-methylbut-1-ene (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Torr). Tsang studied the dissociation of 2,4-dimethylhex-1-ene [11] by SPST (970-1180 K, 1-5 atm) and reported k 3 for dissociation of 2MA.…”
Section: Introductionmentioning
confidence: 99%
“…The dashed line is a simulation using k 6 from Fernandes et al [25]. The dash-dotted line is a simulation using k 6 from Fernandes et al and k 8 from Ye et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…This produces a narrower beam than the HeNe, allowing ~0.2 s more chemical signal to be measured close to t 0 . A new configuration of the shock tube driver section has also recently been implemented [26] and was used to obtain the 1%-concentration dataset. The molar refractivity of Kr is 6.367 cm 3 mol -1 [27], and that of cyclopentane is 22.89 cm 3 mol -1 , which was calculated from its refractive index (1.405) and molar density (0.01071 mol mL -1 ) [28].…”
Section: Methodsmentioning
confidence: 99%
“…The BST is equipped with a diaphragmless driver section that gives excellent reproducibility of shock conditions. 1,2 The diaphragmless driver also significantly reduces turnaround time between experiments, by about an order of magnitude. The BST is highly modular and can be easily reconfigured to implement multiple analytical techniques and types of experiments.…”
Section: Introductionmentioning
confidence: 99%